2016
DOI: 10.1186/s13104-016-2156-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of vibroarthrographic signals in knee osteoarthritis diagnosis training

Abstract: BackgroundVibroarthrographic (VAG) signals are used as useful indicators of knee osteoarthritis (OA) status. The objective was to build a template database of knee crepitus sounds. Internships can practice in the template database to shorten the time of training for diagnosis of OA.MethodsA knee sound signal was obtained using an innovative stethoscope device with a goniometer. Each knee sound signal was recorded with a Kellgren–Lawrence (KL) grade. The sound signal was segmented according to the goniometer da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Previous vibroarthrography-related research also performed in OKC showed that articular surfaces with chondral lesions possess diminished capabilities of friction reduction and generate a distinct VAG waveform pattern compared to those from healthy joints [12, 20, 21]. Accordingly, in our study, knees with chondromalacic changes were characterized by signals with higher amplitude and variation, when compared to the CTRS group.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Previous vibroarthrography-related research also performed in OKC showed that articular surfaces with chondral lesions possess diminished capabilities of friction reduction and generate a distinct VAG waveform pattern compared to those from healthy joints [12, 20, 21]. Accordingly, in our study, knees with chondromalacic changes were characterized by signals with higher amplitude and variation, when compared to the CTRS group.…”
Section: Discussionsupporting
confidence: 49%
“…It is believed that such analysis provides specific information about tribological properties of the joint, related among other factors to hyaline cartilage status and/or rheological characteristics of synovial fluid [18, 19]. Thus, the VAG method provides clinicians insight into mechanical, friction-reducing features of the articular environment, which reflects the overall condition of the joint, with special regard to its function [20]. This broadens the possibilities of physical examination and enables the selection of specific physical therapy interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Kellgren-Lawrence (KL) grade system was developed in Shieh et al (2016) for recording the vibroarthrographic signals to identify knee Osteoarthritis. However, accurate knee osteoarthritis detection was not performed.…”
Section: Related Workmentioning
confidence: 99%
“…In [32][33][34], researchers used sound vibration signals to evaluate the degree of recovery for patellofemoral pain syndrome, OA, and skeletal muscle damage, respectively. In the current study, the receiver positions of the collected signals were based on those used in [32][33][34] and the recommendations of a clinical orthopedic specialist. Figure 1a-c shows a schematic diagram of the measurement process, a photograph of the device, and a diagram of the flexion-to-extension swing measurement, respectively.…”
Section: Signal Capturingmentioning
confidence: 99%
“…Signals processed by a digital convertor in a microcontroller unit (Arduino Uno, Scarmagno, Italy) were transmitted to a computer for processing via a USB 2.0 port. the receiver positions of the collected signals were based on those used in [32][33][34] and the recommendations of a clinical orthopedic specialist. Figure 1a-c shows a schematic diagram of the measurement process, a photograph of the device, and a diagram of the flexion-to-extension swing measurement, respectively.…”
Section: Signal Capturingmentioning
confidence: 99%